A SYSTEMATIC REVIEW OF THE IMPACT OF FLEXIBLE POLICIES ON ORGANIZATIONAL COMMITMENT WITH EMPLOYEE WELL-BEING AS AN INTERVENING VARIABLE - Victorio Chipta Gregory Manus; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2026)
The transformation of modern work systems has positioned work flexibility as a strategic element in strengthening organizational commitment (OC). This study systematically examines the impact of work-life balance (WLB), remote work policies, and flexible scheduling on OC, with employee well-being as a mediating variable. A Systematic Literature Review (SLR) approach was employed, analyzing 77 scholarly articles published between 2019 and 2024. The literature was sourced from Scopus, Web of Science, Emerald, and ScienceDirect databases. Findings indicate that all three dimensions of work flexibility significantly and positively contribute to OC, both directly and through improvements in employee well-being. WLB demonstrably enhances affective commitment; remote work policies promote engagement and technology-driven loyalty; and flexible scheduling supports greater work engagement while reducing work-family conflict. Employee well-being is proven to be a primary mediator in the relationship between work flexibility and OC. This study also identifies conceptual, methodological, and contextual gaps in previous literature and recommends the development of an integrative theoretical model utilizing a multi-path mediation approach. The resulting theoretical and practical implications provide a foundation for the formulation of HR policies focused on well-being and sustainable employment. This review makes a significant contribution to enriching the literature and guiding the theoretical development of HRM in the context of flexible work.